Effects of alloying factors and solidification rate on as-cast microstructure of 2024 aluminum alloy - YI Shanshan; FENG Jiawen; LIU Qiang; XIAO Wenlong; MA Chaoli (Journal of Aeronautical Materials, 2024)
The as-cast microstructure of 2024 high-strength aluminum alloy has an important effect on its thermal workability and end-use performance.The effects of Cu/Mg ratio and solidification rate on as-cast microstructure were investigated by regulating the Cu and Mg content and solidification rate of 2024 alloy. The results show that with the mass ratio of Cu/Mg increases from 2.1 to 4.1，the type of second phase in the alloy is not changed. However，the content of Al2CuMg gradually decreases，while the content of Al2Cu and Al23Cu（Fe，Mn） 4 gradually increases.When the solidification rate increases from 0.2 ℃/s to 2.4 ℃/s，the grain size is obviously refined，the average grain size decreases from 293.0 μm to 77.0 μm. Moreover，the dendrites become developed，and the dendrite arm spacing decreases，and the second phase becomes smaller and distributes more homogeneous in the matrix，and the content of Al23Cu（Fe，Mn） 4 insoluble phase obviously reduces. The formation of iron-rich insoluble phase can be reduced by reducing the Cu/Mg ratio and increasing the solidification rate，so as that the machining and mechanical properties of the alloy can be improved.